European Commission merger control: Combining competition and the creation of larger European firms. (10th November 2013) - Thatcher, Mark
Abstract The article examines the European Commission's use of its legal powers over mergers. It discusses and tests two views. One is that the 'neoliberal' Commission has ended previous industrial policies of aiding 'national champion' firms to grow through mergers and instead pursues a 'merger‐constraining' policy of vigorously using its legal powers to block mergers. The other is that the Commission follows an 'integrationist policy' of seeking the development of larger European firms to deepen economic integration. It examines Commission decisions under the 1989 EC Merger Regulation between 1990 and 2009. It selects three major sectors that are 'likely' for the 'merger‐constraining' view – banking, energy and telecommunications – and analyses a dataset of almost 600 Commission decisions and then individual merger cases. It finds that the Commission has approved almost all mergers, including by former 'national champion' firms. There have been only two prohibitions over 20 years in the three sectors and the outcome has been the creation of larger European firms through mergers. It explains how the Commission can pursue an integrationist policy through the application of competition processes and criteria. The wider implication is that the Commission can combine competition policy with achieving the 'industrial policy' aim of aiding the development of larger European firms.